SOLUBILITY ENHANCEMENT OF GLICLAZIDE BY SOLID DISPERSION METHOD - D. More, Smita; Sontakke, Sneha B. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
In the present research work, an attempt was made to improve the solubility and dissolution rate of a poorly soluble drug, Gliclazide by solid dispersion method using soluplus and kollidon VA64 as a carrier and PEG 4000, sorbitol, cremophor EL as a plasticizer. Evaluation of solid dispersion i.e. in vitro- dissolution, differential scanning calorimetry (DSC), Fourier transform infrared (FTIR), X-ray diffraction (XRD) was performed. The solid dispersion of KollidonVA64 and PEG 4000(1:1) showed the best cumulative drug release (72.16Â±2.01). The solid dispersions were then formulated as tablets and were subjected to various preformulation and post formulations studies. The evaluation of tablet batches i.e. hardness, friability, drug content, in vitro release, and stability parameters have been studied. After the evaluation of all batches, the F4 batch shows the best cumulative release (95.57Â±1.25percent). From this study, it can be concluded that dissolution rate of gliclazide could be enhanced by tablets containing solid dispersion by direct compression technique. KEYWORDS Gliclazide, Solid Dispersion, Fusion Method, Plasticizer.